Comparative evaluation of different types of blood culture media for isolation of aerobes. - Gross, P A (1977)
The possible advantage of hypertonic sucrose medium over isotonic medium for isolating aerobic organisms from blood was studied. Approximately 50 ml of medium and 5 ml of blood inoculum were present in each culture bottle. In the first phase of the study, supplemented peptone broth (SPB) was compared with brucella broth containing 10% sucrose (BB-10S). There were 194 significant clinical isolates in at least one of the two bottles in each set during a 7-month period; 160 (82%) of the isolates grew in SPB, whereas 191 (98%) grew in BB-10S (P less than 0.01). Of the 158 isolates that grew in both media, 13 (8%) appeared earlier in BB-10S, whereas none did so in SPB. In the second phase of the study, SPB with 10% sucrose (SPB-10S) was compared with BB-10S. There were 187 isolates during a 9-month period; 173 (93%) grew in SPB-10S compared with 179 (96%) for BB-10S. In this comparison there was no apparent difference in the time interval required for recovery of organisms. The two hypertonic sucrose media (SPB-10S and BB-10S) were comparable for isolating organisms under aerobic conditions and superior to the nonhypertonic medium (SPB).